Development and characterization of a new fish cell line from Honeycomb grouper, Epinephelus merra - Swaminathan, T Raja; Gopalakrishnan, A; Basheer, V S; Divya, P R; Jena, J K (The Indian Journal of Animal Sciences, 2012)
A new cell line HGF was developed from fin tissue of Epinephelus merra Bloch, 1793. The cell line was maintained in Leibovitz’s L-15 supplemented with 15% FBS and cells have been subcultured 45 times. The HGF cell line consists predominantly of fibroblastic-like cells. The cells were able to grow at temperatures between 25° and 32°C with optimum temperature of 28°C. The growth rate of fin cells increased as the FBS proportion increased from 2 to 20% at 28°C with optimum growth at the concentrations of 15 or 20% FBS. After confluence, the cells were sub-cultured with a split ratio of 1:2. The cells showed fibroblastic-like morphology and reached confluence on the fourth day after subculture. Polymerase chain reaction amplification of mitochondrial 16S rRNA and COI indicated identity of these cell lines with those reported from this animal species, confirming that the cell lines were of honeycomb grouper origin. The cells were successfully cryopreserved and revived at passage numbers 10, 20 and 30. The bacterial extracellular products from Vibrio cholerae MTCC 3904 was found toxic to this cell line.